Two sub-Antarctic and Northern Europe distributed diatom species found in a middle-mountain lake in France. Issue 2 (3rd April 2019) - Heudre, David; Wetzel, Carlos E.; Van de Vijver, Bart; Moreau, Laura; Ector, Luc
ABSTRACT: During a survey of the diatom flora of Longemer Lake (Xonrupt-Longemer, Vosges, France), two species with an unusual biogeographical distribution were observed. Psammothidium abundans, previously considered being a sub-Antarctic endemic but today also found in rivers in Sweden, Ireland and the UK, and Achnanthidium sublineare, up to now confined to northern Europe, were identified. These are the first records of these rare diatom species in France ( A. sublineare ) and in a European lake ( P. abundans ). Since there are only a few illustrations of these two species in the literature, both populations are illustrated using light and scanning electron microscopy in order to provide a detailed morphological account. Details on their actual biogeographical distribution are added.